DOES FINANCIAL LITERACY EFFECT TO PERFOMANCE AND SUSTAINABILITY OF CULINARY MSMEs IN GREATER JAKARTA? - Reny Fitriana Kaban; Martina Safitry (Ekonomi Bisnis, 2020)
Abstract This research aims to find out whether financial literacy effects performance and sustainability of culinary MSME. Respondents are 100 managers or owners of culinary MSMEs in Greater Jakarta who are responsible for making decisions regards the business and selected by purposive sampling. Structured questionnaire consisted of type of quiz modified from the Basic Indonesian Financial Literacy Index to determine financial literacy and modification of the EFQM Excellence Model to measure performance based on the perception of how far the respondent reaches the indicators of business results. Questions of business sustainability is modified from the Triple Bottom Line reporting indicator to measure sustainability of business operations in terms of economic, environmental and social aspects. SEM model is used to analyze data. The result showed financial literacy has a significant effect to performance of culinary MSME as well as the performance has a significant effect to sustainability of culinary MSME. However, financial literacy does not have a significant effect to sustainability of culinary MSME. It is strongly recommended to management of culinary MSMEs to increase their management capacity in term of financial literacy especially ability to be engaged with digital and financial technology.Keywords: Business performance, Culinary MSME, Financial literacy, Sustainability